I know who you are [large type] - Feeney, Alice (Thorndike Press large print core, 2019)
Meet Aimee Sinclair: the actress everyone thinks they know but can't remember where from. But someone knows Aimee very well... they know who she is and they know what she did. When Aimee comes home and discovers her husband is missing, the police think she's hiding something and they're right, she is - but perhaps not what they thought. As Aimee struggles to keep her career and sanity intact, her past comes back to haunt her in ways more dangerous than she could have ever imagined. -- adapted from back cover